CORRUPTION AS A FORM OF ANTISOCIAL CAPITAL (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article analyzes a corruption as a form of antisocial capital. It’s role in the erosion of social capital is determined. The economic nature, preconditions, factors and motives of the formation of the social norms of corruption and bribery are investigated. The essence of corruption is revealed through the relationship between the principal and the agent. The tragedy «Inequality – Mistrust – Corruption» by E. Uslerer is analyzed. The signs of corruption agreement and social mechanisms of its implementation are determined. The dependence of corruption on the culture of different countries is investigated. Based on the analysis of Corruption Perceptions Index (CPI), Bribe Payers Index (BPI), Global Barometer of Corruption by Transparency International and some subindices of the Global Competitiveness Index, the peculiarities of the development of corruption in Ukraine were compared with post-Soviet countries, Western and Eastern Europe. The tendency of state bureaucrats to take bribes, business inclination to bribe and subjective assessment of ordinary citizens regarding the scope and scale of corruption spread in different countries of the world are estimated. The global and national trends in the development of corruption social norms are determined. The main areas of distribution of corruption social norms and their difference for the countries of Eastern and Western Europe are revealed. The peculiarities of the formation of the corruption system «competitive bribery» in Ukraine are analyzed. According to the methodology S. Rose-Ackerman and M. Johnson the problems of forming a competitive bribery and society of the type «Oligarchs and clans» are studied. The spiral of promotion of corruption and its negative consequences for society are analyzed. The network effects of clan economy formation and its features in Ukraine are characterized . The preconditions and readiness of the Ukrainian society to eliminate such a social norm in the national economy are determined at the present stage. Based on the results of the international and national sociological survey, the readiness of the population to abandon such antisocial capital form is assessed and the global trends of public readiness of the fight against corruption in the world are specified.
Keywords: antisocial capital, negative externalities, corruption, corruption social norm, nepotism, clan economy.